The Association between Mycobacterium Tuberculosis Genotype and Drug Resistance in Peru. - Louis Grandjean; Tomotada Iwamoto; Anna Lithgow; Robert H Gilman; Kentaro Arikawa; Noriko Nakanishi; Laura Martin; Edith Castillo; Valentina Alarcon; Jorge Coronel; Walter Solano; Minoo Aminian; et al. (PLoS ONE)
Background The comparison of Mycobacterium tuberculosis bacterial genotypes with phenotypic, demographic, geospatial and clinical data improves our understanding of how strain lineage influences the development of drug-resistance and the spread of tuberculosis. Methods To investigate the association of Mycobacterium tuberculosis bacterial genotype with drug-resistance. Drug susceptibility testing together with genotyping using both 15-loci MIRU-typing and spoligotyping, was performed on 2,139 culture positive isolates, each from a different patient in Lima, Peru. Demographic, geospatial and socio-economic data were collected using questionnaires, global positioning equipment and the latest national census. Results The Latin American Mediterranean (LAM) clade (OR 2.4, p<0.001) was significantly associated with drug-resistance and alone accounted for more than half of all drug resistance in the region. Previously treated patients, prisoners and genetically clustered cases were also significantly associated with drug-resistance (OR's 2.5, 2.4 and 1.8, p<0.001, p<0.05, p<0.001 respectively). Conclusions Tuberculosis disease caused by the LAM clade was more likely to be drug resistant independent of important clinical, genetic and socio-economic confounding factors. Explanations for this include; the preferential co-evolution of LAM strains in a Latin American population, a LAM strain bacterial genetic background that favors drug-resistance or the "founder effect" from pre-existing LAM strains disproportionately exposed to drugs.